Fatigue life modeling of a single crystal superalloy and its thin plate with a hole at elevated temperature. (5th February 2015) - Dong, Chengli; Yu, Huichen; Li, Ying
Highlights: Conduct many fatigue tests of the SC superalloy and its simple structure at 760 °C. Propose two kinds of the modified anisotropic models to predict the LCF life. Improve the life prediction level offered by the modified anisotropic models. The modified models are based on the failure mode and have clear physical meanings. Abstract: Many low cycle fatigue (LCF) experiments of a second generation single crystal (SC) nickel-base superalloy and its thin plate with a hole are carried out to investigate the effects of crystallographic orientation and stress concentration on the LCF life. The local strain approach and two kinds of modified anisotropic models we proposed are employed to predict the fatigue lives for the SC superalloy and its thin plate with a hole. The results show that the LCF lives of the SC superalloy and its thin plate with a hole have strong crystallographic orientation dependence; the local strain approach fails to predict the fatigue lives but the two kinds of modified anisotropic models are able to predict the fatigue lives for the SC superalloy and its thin plate with a hole. However, compared with the modified anisotropic model only considering the interaction of shear strains, the modified one considering both interaction of shear strains and coupling of normal and shear strains has better predicted accuracy.